The distribution and function of GDE2, a regulator of spinal motor neuron survival, are disrupted in Amyotrophic Lateral Sclerosis - Anna Westerhaus (Acta Neuropathologica Communications, 2022)
Abstract Amyotrophic lateral sclerosis (ALS) is a fatal neurodegenerative disease that affects the viability of upper and lower motor neurons. Current options for treatment are limited, necessitating deeper understanding of the mechanisms underlying ALS pathogenesis. Glycerophosphodiester phosphodiesterase 2 (GDE2 or GDPD5) is a six-transmembrane protein that acts on the cell surface to cleave the glycosylphosphatidylinositol (GPI)-anchor that tethers some proteins to the membrane. GDE2 is required for the survival of spinal motor neurons but whether GDE2 neuroprotective activity is disrupted in ALS is not known. We utilized a combination of mouse models and patient post-mortem samples to evaluate GDE2 functionality in ALS. Haplogenetic reduction of GDE2 exacerbated motor neuron degeneration and loss in SOD1 G93A mice but not in control SOD1 WT transgenic animals, indicating that GDE2 neuroprotective function is diminished in the context of SOD1 G93A. In tissue samples from patients with ALS, total levels of GDE2 protein were equivalent to healthy controls; however, membrane levels of GDE2 were substantially reduced. Indeed, GDE2 was found to aberrantly accumulate in intracellular compartments of ALS motor cortex, consistent with a disruption of GDE2 function at the cell surface. Supporting the impairment of GDE2 activity in ALS, tandem-mass-tag mass spectrometry revealed a pronounced reduction of GPI-anchored proteins released into the CSF of patients with ALS compared with control patients. Taken together, this study provides cellular and biochemical evidence that GDE2 distribution and activity is disrupted in ALS, supporting the notion that the failure of GDE2-dependent neuroprotective pathways contributes to neurodegeneration and motor neuron loss in disease. These observations highlight the dysregulation of GPI-anchored protein pathways as candidate mediators of disease onset and progression and accordingly, provide new insight into the mechanisms underlying ALS pathogenesis.